FLUID CATALYTIC CRACKING OF PETROLEUM FRACTION (VACUUM GAS OIL) TO PRODUCE GASOLINE - A-K Mohammed, Abdul Halim; Khalifa Esgair, Karim (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
In this work, fluid catalytic cracking of vacuum gas oil to produce gasoline over prepared faujasite type Y zeolite was investigated using experimental laboratory plant scale of fluidized bed reactor. The catalytic activity of prepared faujasite type NaY, NaNH4Y and NaHY zeolites was investigated. The cracking process was carried out in the temperature range 440 to 500 oC, weight hourly space velocity (WHSV) range 10 to 25 h-1 ,and atmospheric pressure . The catalytic activities of the prepared faujasite type NaY , NaNH4Y and NaHY zeolites were determined in terms of vacuum gas oil (VGO) conversion, and gasoline yield . The conversion at 500oC and WHSV10 hr-1 by using faujasite type NaY, NaNH4Y and NaHY zeolite were 50.2%, 64.1% and 69.5wt% respectively. The gasoline yield using the same operating conditions were 24.8%, 30.5% and 36.8wt% respectively. Gas chromatographic analysis of produced gasoline shows that the paraffin, olefin, and aromatic content change considerably with the end point temperature of gasoline fraction.